Determining Stature Using Hand and Foot Anthropometric Measurements in Young Adults (Journal of Forensic Medicine & Toxicology, 2026)
Introduction: Estimating stature is a crucial aspect of forensic identification, particularly when dealing with fragmented human remains. Due to the impact of ethnicity and regional variations, models tailored to specific populations are cru cial. In India’s varied population, particularly in urban areas such as Delhi, localized information improves precision in medico-legal inquiries. Methods: This study examined the relationship between stature and the anthropometric measurements of the hand and foot in 200 healthy young adults (100 were males, 100 were females) aged 18–25 years. Anthropometric dimensions of the length and breadth of both left and right hands and feet were recorded and analysed. Results: Males exhibited significantly higher average values for all measured parameters (p < 0.05) as compared to females. Insignificant bilateral variations were found, with the exception of foot length in males (p = 0.03). Regarding the relationship between stature and the variables, hand length demonstrated the strongest correlation with stature in males (r = 0.572), while foot length showed the highest correlation in females (r = 0.649). Lower standard errors of estimate suggested that multiple regression models were better than the simple linear models, which confirms hypothesis regard ing the usefulness of measurement of hands and feet in devising unique and better regression models based on sex for forensic stature estimation. Conclusion: The research revealed a significant correlation between height and the dimensions of hand and foot, with left hand length in males and right foot length in females demonstrating the highest accuracy. The bilateral differences were mostly negligible. Multi-regression models surpassed simple linear models, highlighting the importance of inte grated parameters for stature estimation.
Keywords: Hand-breadth; Hand-length; Foot-breadth; Foot-length; Stature